Clinical Outcomes of Extrapleural Closure of a Patent Ductus Arteriosus Concomitant with Aortic Coarctation Repair - Uysal, Ayhan; Tekin, Esra Erturk; Dogan, Omer Faruk (Forum Multimedia Publishing, Llc, 2021)
Background: The aim of this study was to present an extrapleural approach for the closure of patent ductus arteriosus (PDA), with the repair of aortic coarctation (CoA) in the same session, in critically ill newborns and infants as an alternative to the transpleural surgical technique. Methods: Between December 2007 and November 2010, 44 critically ill patients with PDA and coarctation of the aorta were operated on during the same session with the extrapleural approach. The diagnoses of the patients were made by transthoracic echocardiography (TTE). We investigated the aortic arch, the length of the coarctation segment, peak-to-peak gradients, the aortic valve, and intracardiac defects prior to the surgery using TTE. Cardiac angiography was performed to determine whether the patients were suitable for an interventional approach in hemodynamically stable patients. Twenty-eight patients had congestive heart failure with mild to moderate pulmonary and systemic hypertension. The median gestational age and weight of neonates were 2.1 kg (range: 1.4 to 2.9 kg), and 31.4 weeks (range, 28.6 to 37 weeks), respectively. During the operations, PDA was closed using double clips. Resection of coarctation with an extended end-to-end anastomosis was performed in 27 patients. Subclavian flap angioplasty was performed in four patients, and an aortic patch repair was performed in two infants. Postoperative PDA flow and residual aortic gradient were evaluated using echocardiography prior to discharge from the hospital and during the follow-up period. Results: There were three in-hospital deaths (6.8%). During the follow-up period, two patients died (4.8%). The mean follow-up period was 48.3 +/- 21.5 months (range: 29-56 months). Patent foramen ovale, atrial septal defect, and ventricular septal defect were the additional cardiac pathologies. These were hemodynamically insignificant. We detected that the intracardiac defects closed spontaneously. During the follow-up period, recoarctation developed in six patients (20%). We found that the risk factors for recoarctation in patients were to have a gradient from coarctation area, which was higher than >= 50 mmHg, and the length of coarctation segment that was longer than 1 cm in their first operation (P = 0.033). The median time from the first surgery to recoarctation was 25.4 +/- 13.2 months (range: 16-36 months). Balloon dilatation was performed in four patients. We performed redo-surgery in the remaining two patients with recoarctation. The mean intubation time was 9.1 +/- 13.4 hours (range: 5.8-19.8 hours). Transthoracic echocardiography showed normal left ventricular dimensions and systolic function in 34 patients during follow up (87.1%). Conclusion: Our experiences show that surgical repair of aortic coarctation and PDA closure at the same session may be performed safely and with acceptable mortality and morbidity via an extrapleural approach. Interventional approach as a less invasive method may be used in patients who have developed recoarctation.